The crystal structure of ammonium (E)-4-((4-carboxyphenyl)diazenyl)benzoate, C14H13N3O4 - Jian-Ge Wang; Hua-Rui Wang (Zeitschrift für Kristallographie - New Crystal Structures)
C14H13N3O4, monoclinic, I2/a (no. 15), a = 11.4188(4) Å, b = 3.7968(2) Å, c = 30.2320(18) Å, β = 96.037(6)∘, V = 1303.44(11) Å3, Z = 4, Rgt(F) = 0.0656, wRref(F2) = 0.2073, T = 293(2) K.